Young adults with imaginary companions: The role of anthropomorphism, loneliness, and perceived stress. (June 2023) - Yamaguchi, Masanori; Okanda, Mako; Moriguchi, Yusuke; Itakura, Shoji
Abstract: Although adults create and interact with imaginary companions (ICs), little is known about the prevalence of adulthood ICs. Moreover, several studies have focused on the factors associated with creating or sustaining ICs. This study examined the prevalence of adult ICs and their relationship with anthropomorphism, loneliness, and perceived stress, hypothesizing that these variables would correlate with ICs. The participants (154 university students in the pilot study and 500 adults in the main study) completed questionnaires measuring IC status, anthropomorphic tendencies, loneliness, and perceived stress. Approximately 10–15 % of the participants had ICs. We did not detect a robust association between loneliness and having ICs; in contrast, perceived stress and anthropomorphic tendencies explained IC status. The relationship among perceived stress, anthropomorphism, and ICs is discussed. Highlights: Study examined the prevalence of adult imaginary companions (ICs). Relationship of adult ICs with anthropomorphism, loneliness, and perceived stress Questionnaires measuring IC status, anthropomorphism, loneliness, perceived stress Approximately 10–15 % of adults currently have ICs. Perceived stress and anthropomorphic tendencies explained IC status.